2020
DOI: 10.1073/pnas.2009911117
|View full text |Cite
|
Sign up to set email alerts
|

Awareness-driven behavior changes can shift the shape of epidemics away from peaks and toward plateaus, shoulders, and oscillations

Abstract: The COVID-19 pandemic has caused more than 1,000,000 reported deaths globally, of which more than 200,000 have been reported in the United States as of October 1, 2020. Public health interventions have had significant impacts in reducing transmission and in averting even more deaths. Nonetheless, in many jurisdictions, the decline of cases and fatalities after apparent epidemic peaks has not been rapid. Instead, the asymmetric decline in cases appears, in most cases, to be consistent with plateau- or shoulder-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
191
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(219 citation statements)
references
References 29 publications
6
191
0
Order By: Relevance
“…We have focused on scenarios where NPIs are switched off in a step-wise manner, but even a more measured approach in which NPIs are gradually released over a period of many months does not prevent the worse effects (Supporting Information, Section S2). We stress that as hospitalisations and deaths increased we would expect both national legislation and emergent behaviour to limit the spread [21]. Therefore, our scenarios represent a pessimistic view of measures in response to a worsening outbreak.…”
Section: Discussionmentioning
confidence: 96%
“…We have focused on scenarios where NPIs are switched off in a step-wise manner, but even a more measured approach in which NPIs are gradually released over a period of many months does not prevent the worse effects (Supporting Information, Section S2). We stress that as hospitalisations and deaths increased we would expect both national legislation and emergent behaviour to limit the spread [21]. Therefore, our scenarios represent a pessimistic view of measures in response to a worsening outbreak.…”
Section: Discussionmentioning
confidence: 96%
“…The body of modeling work based on the SEIR scheme touches similar themes to those just mentioned, but due to the larger number of articles, there are also some new interesting angles. In particular, we find papers focusing, among other things, on the effects of face masks [82] , [85] , [86] , [87] , [89] , capturing different aspects of NPIs [64] , [67] , [69] , [70] , [71] , [73] , [74] , [75] , [77] , [79] , [80] , [81] , [83] , [84] , [90] , studying the problem of optimal control of the pandemic [72] , [76] , [78] , [88] , investigating approaches to lift measures put in place in the first wave [62] , [63] , [65] , model the possible exposure to the virus via droplets or fomites [91] , [92] , and consider the impact on the health care infrastructure of COVID-19 and seasonal flu in the winter [68] .…”
Section: Epidemic Modelsmentioning
confidence: 99%
“…Reporting on the pandemic cannot be perceived only for its informative function. It is unknown what effect a constant reporting on the cases, casualties and containment methods could have on adherence to distancing rules or mental health 19,[35][36][37][38] . We employed sentiment analysis to study the large volume of identified COVID-19 articles by analyzing emotions they could evoke.…”
Section: Discussionmentioning
confidence: 99%